2019 outburst of 15-Bootids (IAU#923, FBO) and search strategy to find the potentially hazardous comet. (February 2020) - Jenniskens, Peter; Lyytinen, Esko; Johannink, Carl; Odeh, Mohammad; Moskovitz, Nicholas; Abbott, Timothy M.C.
Abstract: The CAMS BeNeLux and UAE Astronomical Camera Network meteor shower surveys detected a FWHM ​= ​1.8-h wide outburst of 15-Bootids on April 21/22, 2019. Both networks had clear skies throughout the night, but only between 21h28m and 00h13m UTC were meteors from this shower detected. The measured orbit is that of a Halley-type or Long-Period comet. If the shower is an encounter with the 1-revolution dust trail of a Long-Period comet, then that parent comet is a potential impact hazard. The long duration of the outburst suggests comparatively high ejection speeds from, presumably, a large nucleus. The orbit offers guidance for early comet recovery and a search strategy is described. The orbital elements resemble those of bright comet C/539 W1, which may be the parent comet. Highlights: An outburst of the 15-Bootids meteor shower was detected in the night of April 21/22, 2019. The outburst is likely the result of an encounter with the 1-revolution dust trail of a potentially hazardous Long-Period comet that is still on approach. The orbital elements resemble those of bright comet C/539 W1, which may be the parent comet.